Pengaruh Faktor Kemudahan Penggunaan dan Tingkat Keamanan Terhadap Perilaku Doom Spending pada Pengguna Shopee Paylater di Kalangan Mahasiswa - Aisya Aswari; Novemy Triyandari; Erna Chotidjah Suhatmi (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
Digital resolution has accelerated fundamental transformations in the retail and financial sectors, which has implications for significant changes in public consumption. E-commerce platforms now provide a diversification of payment methods to optimize the consumer experience, including the implementation of a delayed payment system (paylater). This study aims to analyze the influence of ease of use and perceived security on doom spending behavior among college students using Shopee PayLater. This study adopted a quantitative approach using a survey design as the research method. The data collection process was carried out through a questionnaire instrument distributed to 100 student respondents selected using a purposive sampling technique. Data analysis was conducted using various statistical techniques including instrument validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using SPSS version 25 software. Partially, the ease of use variable did not show a significant influence on student doom spending behavior. Conversely, the security variable showed a significant positive influence on doom spending tendencies among college students using the Shopee PayLater service. When analyzed simultaneously, both the ease of use and security variables showed a positive and significant influence on doom spending behavior of Shopee PayLater users.